2017
DOI: 10.1016/j.appet.2017.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour among nutrition students and social desirability as a confounder

Abstract: Our study shows that social desirability should be considered while assessing eating behaviour among nutrition students, particularly when studying external eating, binge eating and eating self-efficacy. Moreover, when tailoring interventions to reduce the possible effects of eating behaviour on nutritionists and dieticians' practice, we should consider the influence of social desirability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 55 publications
2
16
0
5
Order By: Relevance
“…Only 32 participants (14.1% of the total sample, or 23.4% of those with any LOC grazing) experienced moderate-to-severe LOC grazing, and only 22 participants (9.7% of the sample) experienced marked distress regarding grazing behaviour. The significant, negative association between GRLOC and social desirability (similar to individuals who experience binge eating, or emotional and external eating [50, 51]) indicates that compulsive grazing may be under-reported, due to motivation to give socially desirable responses regarding “appropriate” eating behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Only 32 participants (14.1% of the total sample, or 23.4% of those with any LOC grazing) experienced moderate-to-severe LOC grazing, and only 22 participants (9.7% of the sample) experienced marked distress regarding grazing behaviour. The significant, negative association between GRLOC and social desirability (similar to individuals who experience binge eating, or emotional and external eating [50, 51]) indicates that compulsive grazing may be under-reported, due to motivation to give socially desirable responses regarding “appropriate” eating behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This is a special type of response bias describing a tendency of survey respondents to answer questions in a manner that will be viewed favorably by others and may lead to underreporting of unhealthy lifestyle habits and overreporting of healthy lifestyle habits [33]. This bias makes comparisons and interpretation of average tendencies difficult and has been well described in students of nutrition and dietetics [34]. It can be assumed that the issue of social desirability bias applies also for students and employees of other health professions.…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, bulimic symptoms are likely to have negative valence. As such, individuals are likely to experience binge eating as embarrassing [ 53 ] and socially undesirable [ 54 ]. Furthermore, studies across cultures revealed that individuals are more likely to avoid negative emotions than positive ones [ 55 ].…”
Section: Discussionmentioning
confidence: 99%